PERTUMBUHAN ANAKAN KOPI (Coffea arabica Lin.) BERBASIS SISTEM AGROFORESTRI DI HUTAN RAKYAT CIMARIAS SUMEDANG - Sri Wilujeng; Ina Darliana; Raizal Fahmi Solihat; Tatang Rohmat (Lambung Mangkurat University-Indonesia, 2021)
In the recent years, there is a significant increase on economic value of coffee as trade commodity. On that note, the most frequently used cultivation practices for coffee in Indonesia is coffee agroforestry system in private forest. However, there are still some constraints in the system development due to the traditional farmer limited knowledge of coffee cultivation practices. In this study we conducted preliminary observations on the coffee cultivation practices used by the traditional farmers to determine the steps needed to improve the coffee quality and sustainability. We study the effect of plant-spacing and shading on the growth of juvenile plant of coffee (Coffea arabica Lin.) from Sigarar utang variety. The observation was carried out in private forest of Cimarias village Sumedang district for 1 (one) month. We used the combination of 2,5m x 2,5m and 3m x 3m for plant-spacing with kayu afrika (Meisopsis eminii Engl.) as shade and without shade. This experiment used Completely Randomized Design experiment with 10 replication for each treatment, with juvenile height (cm), stem diameter (mm), and the quantity of productive primary branches as data. Then data were analyzed using Anova, Duncan’s Multiple Range Test (DMRT) 0,05, and Pearson Correlation. From the result, the best growth of juvenile plant of coffee tree was showed on 3m x 3m spacing with shade. However, the growth shown has not reached the potential of the coffee from Sigarar utang variety as supposed to in accordance with the environmental condition of the crop. This analysis also supports the prediction of low-productivity because there is positive correlation between juvenile height and the quantity of primary branches, and between stem diameter and the quantity of primary branches.